Start of the dry season as a main determinant of inter-annual Mediterranean forest production variations - Maselli, Fabio; Cherubini, Paolo; Chiesi, Marta; Gilabert, María Amparo; Lombardi, Fabio; Moreno, Alvaro; Teobaldelli, Maurizio; Tognetti, Roberto (Agricultural and Forest Meteorology, 2014)
Recent investigations have highlighted the dependence of Mediterranean forest production on spring rainfall. The current work introduces the concept of the start of the dry season (SDS) and performs a three-step analysis to determine the effect of SDS on Mediterranean forest production. Seven forest zones of Tuscany (Central Italy), which present differently pronounced Mediterranean features, are considered. First, a statistical analysis investigates the influence of spring water budget on forest Normalized Difference Vegetation Index (NDVI) inter-annual variations during July–August. The analysis is then extended to assess the impact of inter-annual SDS variability on forest gross primary production (GPP) simulated by a NDVI driven parametric model, modified C-Fix. These simulations lead to rank the considered forest types according to the relevance of SDS in regulating inter-annual GPP variations. The application of similar statistical analyses to detrended tree ring-width time series of typical Tuscany forests confirms the existence of an eco-climatic gradient in the functional relevance of SDS. The influence of SDS on tree growth is attenuated moving from Mediterranean arid to temperate humid environments. These findings are examined and interpreted from an eco-physiological viewpoint taking into consideration the peculiarity of Mediterranean forest ecosystems. Next, relevant implications are discussed in view of the possible consequences of ongoing climate change.
Keywords: Dry season; GPP; Mediterranean forests; Modified C-Fix; NDVI; Ring-widths

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; Innes, John L (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; INNES, JOHN L. (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Responses to elevated atmospheric CO2 concentration and nitrogen supply of Quercus ilex L. seedlings from a coppice stand growing at a natural CO2 spring - Tognetti, Roberto; Johnson D., Jon (Ann. For. Sci., 1999)
Quercus ilex acorns were collected from a population of trees with a lifetime exposure to elevated atmospheric CO2 concentration (CO2), and after germination seedlings were exposed at two [CO2] (370 or 520 μmol mol-1) in combination with two soil N treatments (20 and 90 μmol mol -1 total N) in open-top chambers for 6 months. Increasing [CO2 ] stimulated photosynthesis and leaf dark respiration regardless of N treatment. The increase in photosynthesis and leaf dark respiration was associated with a moderate reduction in stomatal conductance, resulting in enhanced instantaneous transpiration efficiency in leaves of seedlings in CO2 enriched air. Elevated [CO2] increased biomass production only in the high-N treatment. Fine root/foliage mass ratio decreased with high-N treatment and increased with CO2 enrichment. There was evidence of a preferential shift of biomass to below-ground tissue at a low level of nutrient addition. Specific leaf area (SLA) and leaf area ratio (LAR) decreased significantly in leaves of seedlings grown in elevated [CO2] irrespective of N treatment. Leaf N concentration decreased significantly in elevated [CO2] irrespective of N treatment. As a result of patterns of N and carbon concentrations, C/N ratio generally increased with elevated [CO2] treatment and decreased with high nutrient supply. Afternoon starch concentrations in leaves did not increase significantly with increasing [CO2], as was the case for morning starch concentrations at low-N supply. Starch concentrations in leaves, stem and roots increased with elevated [CO2] and decreased with nutrient addition. The concentration of sugars was not significantly affected by either CO 2 or N treatments. Total foliar phenolic concentrations decreased in seedlings grown in elevated [CO 2] irrespective of N treatment, while nutrient supply had less of an effect. We conclude that available soil N will be a major controlling resource for the establishment and growth of Q. ilex in rising [CO 2] conditions
Keywords: carbon physiology; elevated [CO2]; natural CO2 springs; nitrogen; Quercus ilex

Seasonal embolism and xylem vulnerability in deciduous and evergreen Mediterranean trees influenced by proximity to a carbon dioxide spring - Tognetti, Roberto; Longobucco, Anna; Raschi, Antonio (Tree Physiology, 1999)
We investigated how proximity to natural CO2 springs affected the seasonal patterns of xylem embolism in Quercus ilex L., Quercus pubescens Willd., Fraxinus ornus L., Populus tremula L. and Arbutus unedo L., which differ in leaf phenology and wood anatomy. Xylem embolism was evaluated in both artificially dehydrated branches and in hydrated apical branches collected at monthly intervals during a 20-month sampling period. Initial specific hydraulic conductivity was also evaluated. We found species-dependent differences in xylem hydraulic properties in response to elevated CO2 concentration. Populus tremula was the most embolized and A. unedo was the least embolized of the species examined. Effects of elevated CO2 were significant in Q. pubescens, P. tremula and A. unedo, whereas the overall response to elevated CO2 was less evident in F. ornus and Q. ilex. Specific hydraulic conductivity differed among species but not between sites, although the interaction between species and site was significant. Differences in xylem vulnerability between trees growing near to the CO2 spring and those growing in control areas were small. Although differences in hydraulic properties in response to elevated CO2 concentration were small, they may be of great importance in determining future community composition in Mediterranean-type forest ecosystems. The possible causes and ecological significance of such differences are discussed in relation to elevated CO2 concentration and other environmental conditions.
10.1093/treephys/19.4-5.271
Keywords: cavitation; CO2 springs; diffuse-porous; Global change; hydraulic conductivity; Mediterranean-type ecosystems; ring-porous; semiring-porous

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J. D. (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J D (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds